Islamic Education Methodology In An Indisciplinary Perspective - Khoirun Nisa'; Anis Trianawati (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
As the age of religion progresses, it must be able to be examined academically and serve more than just as an assertion of doctrine. As previously stated, the phenomenon of human diversity must also be viewed from the historical perspective of how individuals and groups have understood and interpreted the norms of the religious teachings they adhere to, in addition to how normative the teachings of revelation are. The purpose of this work is to establish the technique for interdisciplinary Islamic studies as well as comprehend Islam in Indonesia. This study combined a library research strategy with descriptive qualitative methods. According to the study's findings, Indonesian Muslims think and understand Islam according to three different patterns. The text is the first. Religion is comprehended and used in accordance with the text's lafdhiyah (literal sound), or